FINANCIAL REPORTING AS AN INFORMATION BASE FOR MANAGEMENT DECISIONS IN TERMS OF FINANCIAL INSTABILITY - E. Sedova; A. Khrisanfova (Вестник университета)
The article considers the contents of different forms of financial statements, their significance in financial analysis and management decisions. The basic requirements to the financial reporting are listed. The article outlines the role of the financial analysis as an important element of financial management in terms of uncertain economic situation.